The fabric of the city : a social history of cloth manufacture in medieval Ypres - Stabel, Peter, 1962- (Turnhout : Brepols, 2022)
Ypres, the most important cloth city in thirteenth-century Europe, provides the ideal example for unravelling how cloth shaped social relations in the medieval city.0Textile industries were one of the driving forces of the urbanisation process in medieval Northwest Europe, and nowhere was their impact so profound as in Flanders, where almost all larger and smaller cities were involved in manufacturing woollens from the 12th to the 16th century. Ypres, the third city in the county, was perhaps the most important concentration of industrial labour and capital in this period. In their heyday in the 13th and 14th centuries Ypres woollens were exported all over Europe and Ypres entrepreneurs and textile workers were able to adapt in very flexible ways to changes in demand. This book investigates not only what the impact of cloth manufacture was on urban society, it also tries to unravel the social mechanisms of industrial development in late medieval cities. It focuses on social inequalities and on the often difficult relationship between the various stakeholders in the urban cloth industry: merchants, entrepreneurs, guild masters and skilled and unskilled workers. Through the analysis work practices, wage levels, investment strategies, gender issues and political aspirations, it unravels how urban industries in the pre-industrial era shaped social relations in the city, how they moulded the urban fabric.
Gloss.